2016
DOI: 10.1051/0004-6361/201322261
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental M-dwarf parameters from high-resolution spectra using PHOENIX ACES models

Abstract: M-dwarf stars are the most numerous stars in the Universe; they span a wide range in mass and are in the focus of ongoing and planned exoplanet surveys. To investigate and understand their physical nature, detailed spectral information and accurate stellar models are needed. We use a new synthetic atmosphere model generation and compare model spectra to observations. To test the model accuracy, we compared the models to four benchmark stars with atmospheric parameters for which independent information from int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 44 publications
4
49
0
Order By: Relevance
“…Assuming that the curves of growth of the lines present in the spectrum do not saturate, we can convert the value of β into an additive number for the metallicity through ∆[Fe/H] = log(β). The metallicity of Proxima is close to solar, as Passegger et al (2016) Koleva & Vazdekis (2012), the metallicity of GJ65 is sub-solar at ([Fe/H] = −0.42 ± 0.10), which is at 2σ from our mean value. But this value is derived from model fitting on a low-resolution combined spectrum of A and B (R = 1000, ∆v ≈ 160 km s − 1), which likely biases [Fe/H] toward lower values for these fastrotating stars.…”
Section: Projected Rotational Velocities Heliocentric Radial Velocitsupporting
confidence: 46%
“…Assuming that the curves of growth of the lines present in the spectrum do not saturate, we can convert the value of β into an additive number for the metallicity through ∆[Fe/H] = log(β). The metallicity of Proxima is close to solar, as Passegger et al (2016) Koleva & Vazdekis (2012), the metallicity of GJ65 is sub-solar at ([Fe/H] = −0.42 ± 0.10), which is at 2σ from our mean value. But this value is derived from model fitting on a low-resolution combined spectrum of A and B (R = 1000, ∆v ≈ 160 km s − 1), which likely biases [Fe/H] toward lower values for these fastrotating stars.…”
Section: Projected Rotational Velocities Heliocentric Radial Velocitsupporting
confidence: 46%
“…Spectra of the PHOENIX-ACE model are computed with the Ames TiO list by Schwenke (1998), whereas BT-Settl model uses TiO line list by Plez (2008). We find that TiO bands matched somewhat better with Plez (2008) as compared to what Passegger et al (2016) have reported. Also, the large differences in T eff could be due to different solar metallicities as mentioned by Passegger et al (2018) and Rajpurohit et al (2014).…”
Section: Analysis and Discussionmentioning
confidence: 52%
“…fr/Grids/BT-Settl/CIFIST2011_2015/. Proxima's surface gravity and metallicity are compatible within the error bars with values of log g = 5.0 and [Fe/H] = 0.0 (Passegger et al 2016), which are part of the BT-Settl model grid, and those were adopted in our SED fitting procedure. The free parameters of the fit were the effective temperature and the angular diameter.…”
Section: Rieke Et Al (2004)mentioning
confidence: 68%